Photodynamic therapy activity of 5, 10, 15-tris(5-bromo-2-thienyl), 20(phenylcarboxy)porphyrin conjugated to graphene quantum dot against MCF-7 breast cancer cells. Issue 7 (18th April 2022) - Makola, Lekgowa Collen; Nwahara, Nnamdi; Managa, Muthumuni; Nyokong, Tebello
Abstract: A novel 5, 10, 15-tris(5-bromo-2-thienyl), 20(phenylcarboxy)porphyrin and its gallium derivative have been synthesized and fully characterized by various spectroscopic techniques and their respective photophysical and photochemical properties, such as the singlet oxygen quantum yield (ΦΔ ), fluorescence quantum yield (ΦF ) and triplet lifetime (τT ) were determined. The complexes were conjugated to PEI_GQDs resulting is stable conjugates, owing to strong π–π stacking interaction between the PEI_GQDs and the porphyrins. PDT studies were carried out on these nanoconjugates and results obtained indicated they are suitable candidates for further in-depth PDT studies. GRAPHICAL ABSTRACT: UF0001